Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1158/1078-0432.ccr-21-0685
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity and Efficacy of Concurrent Androgen Deprivation Therapy, Pelvic Radiotherapy, and Radium-223 in Patients with De Novo Metastatic Hormone-Sensitive Prostate Cancer

Abstract: Purpose: Radium-223 is an alpha-emitting radionuclide associated with overall survival (OS) improvement in metastatic castration-resistant prostate cancer (mCRPC). External beam radiotherapy (EBRT) to prostate extends OS in men with metastatic hormone-sensitive prostate cancer (mHSPC) limited to less than 4 metastases. We hypothesized that combination radium-223 + pelvic EBRT could safely deliver maximal radiotherapy doses to primary and metastatic prostate cancer and may improve disease cont… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Ionizing radiation agents have been used for years in cancer treatment for their direct cytocidal effect on tumor cells, but they are also known to cause inflammation and modulate the host’s immune response to cancer [ 25 , 26 ]. Several studies have shown the hematological toxicity of 223 Ra [ 11 , 27 ]. Furthermore, Pike et al have shown that lymphopenia induced by prolonged extracranial radiotherapy treatment can decrease OS in patients receiving immune checkpoint inhibitors [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ionizing radiation agents have been used for years in cancer treatment for their direct cytocidal effect on tumor cells, but they are also known to cause inflammation and modulate the host’s immune response to cancer [ 25 , 26 ]. Several studies have shown the hematological toxicity of 223 Ra [ 11 , 27 ]. Furthermore, Pike et al have shown that lymphopenia induced by prolonged extracranial radiotherapy treatment can decrease OS in patients receiving immune checkpoint inhibitors [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Such studies are relatively uncommon compared to single-field studies, due to their additional experimental complexity and the limited clinical applicability as most patient treatments are delivered with a single modality. However, recent interest in combining different radiation qualities (including X-rays and alpha particle emitting radionuclides 17 , 18 , X-ray and protons 19 , 20 , and multi-ion treatments 21 ) have provided an impetus to explore this in greater detail.…”
Section: Introductionmentioning
confidence: 99%